Kontra Intelijen Aksi Spionase Siber Terhadap Anggota Democratic National Committee Menjelang Pemilihan Presiden AS Tahun 2016 - Setiyadi, Basuki Erwin; Keliat, Makmur (Jurnal Kajian Stratejik Ketahanan Nasional, 2020)
This research is a case study of cyber espionage conducted against the member of Democratic National Committee (DNC) towards the 2016 US presidential election, caused Hillary Clinton's email leaked and published by WikiLeaks. It indicates the intelligence activities have entered into cyberspace and can disrupt the national ressilience, so it is necessary to do counterintelligence as an effort to maintain the cyber security. This research uses qualitative approach, data collected from interviews and literature study. The purposes of this research are (1) to determine the threat level of cyber espionage conducted against DNC, (2) counterintelligence methods against the threat, (3) and Indonesian Government Strategy against cyber threat. This research use counterintelligence theory, threat analysis theory, and SWOT analysis. The results of this research are (1) the threats analysis of cyber espionage indicating the threat agent has high level threat, it could harms the national interest and affect the national ressilience, (2) cyber counterintelligence are conducted by two ways i.e., defensive counterintelligence to block and detect enemy's access activity, and offensive counterintelligence to collect informations, manipulate, control, and thwart enemy’s action, (3) Indonesian Government Strategies against cyber threat are strengthening legal measure, technical measure, organizational measure, capacity building, and cooperation. Keywords : counterintelligence; cyber espionage; democratic national committee; email; hillary clinton.